Biomimetic nanoceramics in clinical use : from materials to applications - 498464 Vallet-Reg,̕ Maria; Arcos, Daniel; Royal Society of Chemistry (Great Britain) (Cambridge, UK : RSC Pub., 2008)
Includes bibliographical references and index.